2012
DOI: 10.1111/j.1365-2966.2012.21861.x
|View full text |Cite
|
Sign up to set email alerts
|

On the masses of OJ287 black holes

Abstract: Two multifrequency campaigns were carried out on OJ287 in 2005: in April when it was in its pre-outburst state, and in November, during the main 12 yr cycle outburst. The wavelength coverage was from radio to X-rays. In the optical-to-UV range the differential spectrum between the observations has a bremsstrahlung spectral shape, consistent with gas at $3 \times 10^{5}K$ temperature. Our result supports the hydrogen column density of the OJ287 host galaxy of $\sim9.3\times 10^{20} cm^{-2}$, the average value f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 73 publications
4
83
1
Order By: Relevance
“…If we do assume an angle offset of about 15 degrees, the calculated values match the observations. In this model the magnetic field of the optical emission region lies more or less parallel to the jet, as was also concluded in a previous work (Valtonen & Wiik 2012) internal extinction in the OJ287 host galaxy (Valtonen et al 2012a). Since the properties of the helix cone are now fully determined by the optical data, we may apply the model to radio data.…”
Section: The Helix Modelmentioning
confidence: 56%
“…If we do assume an angle offset of about 15 degrees, the calculated values match the observations. In this model the magnetic field of the optical emission region lies more or less parallel to the jet, as was also concluded in a previous work (Valtonen & Wiik 2012) internal extinction in the OJ287 host galaxy (Valtonen et al 2012a). Since the properties of the helix cone are now fully determined by the optical data, we may apply the model to radio data.…”
Section: The Helix Modelmentioning
confidence: 56%
“…The rotation about the common center and the piercing of the primary black hole accretion disk by the secondary black hole results in twin outbursts in the light-curve with a (quasi-) periodicity of about 12 yr (Valtonen et al 2012;Pihajoki 2014). The last outburst happened during the period of 2005-07, and was nicely traced.…”
Section: Oj287mentioning
confidence: 99%
“…Based on the radio core size and the time delay between the radio band and γ-ray band, Karamanavis (2017) found that the γ-ray active region is located at 1.9±1.1 pc away from the jet base for PKS 1502+106, which is quite consistent with our estimates of ∼2 pc in this work. The correlation between the millimeter and the γ-ray light curves also indicates that the γ-ray emitting region should be located at >14 pc (Agudo et al 2011a) for OJ 287, which roughly corresponds to~R 10 4 S for the BH mass of ☉ M 10 10 (e.g., Valtonen et al 2012). …”
Section: Conclusion and Discussionmentioning
confidence: 99%